Gambaran Pengetahuan, Sikap, dan Tindakan Ibu dalam Upaya Pencegahan Acute Kidney Injury (Gagal Ginjal Akut) Pada Anak di Wilayah Kerja Puskesmas Mokoau Tahun 2023 - Grysh Claudia Suharmin; Hartati Bahar; La Ode Liaumin Azim (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Acute Kidney Injury (AKI) in children is a global concern, with cases reported in Panama, India, Haiti, and Nigeria. In Indonesia, the incidence significantly increased in 2022, raising concerns about the importance of prevention. This study aims to describe the knowledge, attitudes, and actions of mothers in preventing Acute Kidney Injury (AKI) in children in the working area of Mokoau Health Center in 2023. The research method used is descriptive qualitative with a phenomenological approach. Data were collected through interviews with five mothers of children aged 0-5 years and one general practitioner at Mokoau Health Center. The findings indicate that mothers' knowledge of Acute Kidney Injury (AKI) is still limited, and their attitudes are generally concerned but not very proactive. Preventive actions taken are still suboptimal, with mothers often relying on self-care before seeking medical help when the condition worsens. This is due to the lack of available information and insufficient access to adequate health education. These findings highlight the need for enhanced health education to improve awareness and the effectiveness of preventive measures among mothers.